1994
DOI: 10.1002/food.19940380110
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of isothiocyanates with egg white proteins

Abstract: SummaryGlucosinolates and their very highly reactive breakdown products (mainly isothiocyanates = ITC) belong to one of the most important natural toxicants. This paper deals with the interactions of allyl-, butyl-, phenyl-and benzyl ITC with egg white proteins resulting in the formation of ITC-proteinconjugates. The ITC's react with amino groups by forming thiourea derivatives. Such reactions are well described by changes in the amounts of free amino groups and available lysine. Further reaction sites are sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…A second effect was a reduced tryptic degradability, and the authors hypothesized that some of the OH functions of tyrosine may be modified 79. The reduced tryptic digestibility of proteins caused by isothiocyanate modification at pH values between 7.5 and 9 was also reported by other groups and has been attributed to a modification of lysine and probably arginine side chains 166b. 170 Additionally, the nitrogen atom of the secondary amine tryptophan can also be a target for modification by isothiocyanates.…”
Section: Reactivity Of Glucosinolate Breakdown Productsmentioning
confidence: 85%
See 1 more Smart Citation
“…A second effect was a reduced tryptic degradability, and the authors hypothesized that some of the OH functions of tyrosine may be modified 79. The reduced tryptic digestibility of proteins caused by isothiocyanate modification at pH values between 7.5 and 9 was also reported by other groups and has been attributed to a modification of lysine and probably arginine side chains 166b. 170 Additionally, the nitrogen atom of the secondary amine tryptophan can also be a target for modification by isothiocyanates.…”
Section: Reactivity Of Glucosinolate Breakdown Productsmentioning
confidence: 85%
“…Kroll et al. (1994) demonstrated that a similar isothiocyanate concentration (15.2 μmol benzyl isothiocyanate per gram of protein) reduced the available lysine content of the egg white by 6.6 % 166b. Therefore, these reactions will occur in sulfur‐ or lysine‐rich foods in a combination with ingredients/side dishes from Brassica plants and for example meat or eggs, and it is expected that modified proteins will be of lower nutritional quality.…”
Section: Reactivity Of Glucosinolate Breakdown Productsmentioning
confidence: 99%
“…The basis for the distribution of ITCs throughout the body is the reversibility of their binding to amino-and thiol-groups and especially the high degree of binding to cysteine and GSH [162,163,181,194]. The resulting thioldisulphide exchange give rise to an enormous range of possible intermediates and transport forms of ITCs, e.g.…”
Section: Distributionmentioning
confidence: 99%
“…A less explored area is the role of other food components on bioavailability of ITCs during consumption of vegetables, as it happens in a regular meal. ITCs can react with free amino groups and sulfhydryl side chains of proteins, potentially reducing ITC bioaccessibility. On the contrary, an in vivo study showed that after consumption of a whole meal that included meat, the absorption of ITC was between one‐ and fivefold higher compared to ingestion without meat depending on the type of ITC .…”
Section: Introductionmentioning
confidence: 99%